Licenciamento ambiental nos municípios da Grande Aracaju : desafios e possibilidades - Costa, Gecássia Maria da (2015)
This study aims to analyze the feasibility of the Shared Environmental Management , in particular the Environmental Licensing tool and its interaction with the municipalization in the State of Sergipe . We chose to study the Greater Aracaju , for the same occupy most of the state´s population , and that in this region are located 60 % of state industries , the largest industrial center of the state federation , which contributes to the environmental degradation process more intensified , and also contain the state capital, as a reference for the rest of the municipalities. The theoretical approach is based on an analysis of the environmental context through the Federal Constitution and laws and regulations , as well as the concept of environmental management and environmental management in municipalities. The methodological approach was performed literature as well as on-site visit in all municipalities of the region studied. After theoretical and methodological discussion this study comes to the conclusion that we need to develop strategies to improve environmental management in the aforementioned region in view of the precarious reality found and points the public consortium as a model of environmental regional development and improvement of the State Environmental Policy .